Aktivitas Enzim Inulinase dan Laju Pertumbuhan Spesifik Isolat Bakteri IS-1 pada Medium Tepung Umbi Dahlia - Wijanarka Wijanarka; Maulida Aqlia; Kristina Kristina (Jurusan Biologi FMIPA Universitas Cenderawasih, 2018)
Dahlia bulbs (Dahlia variabilis) contains carbohydrates in the form of inulin. Inulin is a form of fructose polymer from fructose monomers. Inulin hydrolysis produces a product in the form of fructose.Inulinase enzyme is an enzyme able to purely hydrolyze inulin. This study aims to determine the activity of inulinase enzymes and the specific growth rate of IS_1 bacterial isolates producing inulinase in medium of Dahlia tuber flour. Isolates of inulinase-producing bacteria were isolated directly from decay dahlia tubers and used as an inoculum in creating starter.The measurement of cell growth was carried out by inoculating a 20-hour starter on the production medium. Incubation is done for 24 hours using a rotary shaker with a speed of 120 rpm. Sampling was carried out every 4 hours at 0-hour (T0), 4 hours (T4), 8 hours (T8), 12 hours (T12), 16 hours (T16), 20 hours (T20) and 24 hours (T24) intervals with a sample of 5 mL measured for absorbance of λ 520 nm using spectrophotometer. Production medium culture in each sample was taken 1 mL and centrifuged at 3000 rpm for 10 minutes to obtain supernatant of crude enzyme. Measurement of inulinase enzyme activity was carried out using 3,5-dinitrosalicylic acid (DNS) method and spectrophotometric method at λ 570 nm. IS_1 bacterial isolate showed optimum growth at incubation time of 8 hours with OD of 0.647 and had a specific growth rate (µ) of 0.02 / hour with a generation time of 34.65 hours. The highest enzyme activity produced by IS_1 bacteria at 8 hours incubation time was 0.490 IU. The conclusion of this study is that IS_1 bacteria indicates good growth in medium of dahlia tuber flour and has inulinase enzyme activity which is able to hydrolyze inulin into fructose. Key words: inulin, bacterial isolate, inulinase, production